XOR Logic Gate by Carbon/Metal Nanoinks Based on a Double-Stage Optical Kerr Gate Configuration - J. A. García-Merino; E. Feria-Reyes; C. Mercado-Zúñiga; M. Trejo-Valdez; C. R. Torres-San Miguel; J. R. Vargas-García; C. Torres-Torres (Advances in Condensed Matter Physics)
Two-input binary exclusive-or logic operations were presented by the assistance of multiwall carbon nanotubes in a double-stage optical Kerr gate scheme with two control beams. The samples were prepared by the aerosol pyrolysis method and decorated by platinum nanoparticles using a chemical vapor deposition technique. The nanostructures were suspended in ethanol to obtain carbon/metal nanoinks with different concentrations and then randomly distributed networks integrated in thin film form were fabricated. Polarization-selectable functions were obtained in the double-stage scheme by using nanosecond third-order nonlinear optical effects at 532 nm wavelength exhibited by the samples. Potential applications for ultrafast identification and encryption of nonlinear optical signals were discussed.